Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/en14092656
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Additive Assisted Fabrication of Compact and Ultra-Smooth Perovskite Thin Films with Fast Lamp Annealing

Abstract: Perovskite solar cells (PVSC) have drawn increasing attention due to their high photovoltaic performance and low-cost fabrication with solution processability. A variety of methods have been developed to make uniform and dense perovskite thin films, which play a critical role on device performance. Herein, we demonstrate a polymer additive assisted approach with Polyamidoamine (PAMAM) dendrimers to facilitate the growth of uniform, dense, and ultra-smooth perovskite thin films. Furthermore, a lamp annealing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Shaik et al used PAMAM as an additive to prepare the precursors. 86 The amine functional groups of PAMAM could chelate with Pb 2+ in the precursor solution and inhibit the nucleation and growth of the perovskite along the (110) direction, which influenced the crystallization kinetics of the MAPbI 3 perovskite. Narendhiran et al reported a method of using PVDF-HFP as an additive.…”
Section: Additive-controlled Growthmentioning
confidence: 99%
“…Shaik et al used PAMAM as an additive to prepare the precursors. 86 The amine functional groups of PAMAM could chelate with Pb 2+ in the precursor solution and inhibit the nucleation and growth of the perovskite along the (110) direction, which influenced the crystallization kinetics of the MAPbI 3 perovskite. Narendhiran et al reported a method of using PVDF-HFP as an additive.…”
Section: Additive-controlled Growthmentioning
confidence: 99%
“…Silicon solar cells are widely used, but there is considerable research being done with the aim of providing less expensive solar cells, such as polymer solar cells and perovskite solar cells. [94][95][96][97].…”
Section: Solar and Fuel Cells As An Energy Production Application Of ...mentioning
confidence: 99%